Effect of Different Concentrations of Propylene Glycol and Glycerin on the Formulation of Guava Leaf (Psidium Guajava Linn.) Body Scrub with White Rice (Oryza sativa Linn.) - Budi Setiawan; Renatalia Fika; Mazaya Fadhila; Mevy Trisna; Lovyola Adma Putri (Jurnal EduHealth, 2023)
Guava leaves (Psidium guajava Linn.) have contents such as saponins, essential oils, tannins and anti-mutagenic and antioxidants which are ingredients that can reduce free radicals to cells. White rice (Oryza sativa Linn.) is a material that can be used as an abrasiver. Besides being easy to find, white rice also has a relatively cheap price, compared to brown rice or others. This study aims to determine the ethanol extract of guava leaves with white rice can be formulated and the effect of glycerine-propylenglycol in the preparation of body scrub cream with each concentration of 1%, 3%, and 5% and vice versa 5%, 3%, and 1% which are made in 3 formulas. The results obtained from the evaluation of the preparation are: Organoleptical test FI (green), FII and FIII (brown). Homogeneity test obtained by the three formulas is homogeneous, pH test obtained that all formulas meet the pH requirements of 4.5 - 6.5. The spreadability test obtained results in FI (3.1 cm), FII (3.2 cm), FIII (3.0 cm). As for the determination of the type (type) of emulsion obtained that all formulas have type m/a.